Improvisation and Music Education: From the Sonic to Social Attunement - Vanja Dabic (Jurnal Kajian Seni, 2021)
In order to create a relationship to music, artists first need to create a relationship with their inner sound, and the way in which they approach the manifestation of sound from their instrument (whether it'd be through the use of hands, voice, or a plain manifestation of thoughts). Since this process is dialectic in its nature, the ability to develop this type of responsiveness, sometimes referred to as "attunement", is as important in the musical sphere as it is in social exchanges. Therefore, musical practice can play an important role in developing such aptitude among people of all ages. This paper focuses on the factors that stimulate or inhibit expression, through the lens of western classical and Javanese gamelan musical practice. It will be argued that the change of awareness in individual experience, gained through music improvisation can find its reflection on the interactive synchrony in a larger social and cultural frame.